2020
DOI: 10.1002/marc.202000001
|View full text |Cite
|
Sign up to set email alerts
|

Strong Interface Construction of Carbon Fiber–reinforced PEEK Composites: An Efficient Method for Modifying Carbon Fiber with Crystalline PEEK

Abstract: In order to improve the poor solvent resistance and poor temperature resistance caused by traditional sizing agents, crystalline poly(ether ether ketone) (PEEK) is introduced to the interfacial phases of carbon fiber (CF) reinforced PEEK composites by a soluble precursor named PEEK‐1,3‐dioxolane. By changing the soluble precursor molecular weight and concentration in the sizing solution, the content of PEEK coated on the CF fiber surface can be controlled and the different interfacial properties of the PEEK co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…5,8 The mechanical properties of the ternary composites could be additionally improved by increasing the level of interfacial adhesion between fibers and the polymer matrix. 47 This was achieved chemically by treating fibers or loading with various agents or nanoparticles. According to many authors, the last way provided a synergistic effect.…”
Section: The Tribological Propertiesmentioning
confidence: 99%
“…5,8 The mechanical properties of the ternary composites could be additionally improved by increasing the level of interfacial adhesion between fibers and the polymer matrix. 47 This was achieved chemically by treating fibers or loading with various agents or nanoparticles. According to many authors, the last way provided a synergistic effect.…”
Section: The Tribological Propertiesmentioning
confidence: 99%
“…For example, Yuan et al 23 synthesized semi‐aliphatic polyimide as CF sizing agent, and the interlaminar shear strength (ILSS) and flexural strength of CF/PEEK raised by 23.8% and 7.8%. Yang et al 24 found that after PEEK‐1,3‐dioxolane sizing agent coated on CF, the interfacial shear strength (IFSS) of CF/PEEK improved by 91.5%.…”
Section: Introductionmentioning
confidence: 99%
“…When treated by SVA, PEEK chains have more mobility and rearrange themselves toward the equilibrium state, which relieves internal stress. [ 40,47,48 ] Along with the stress releasing, the conformation of PEEK chains increased. The chains prefer to form coiled conformations, which caused the shrinkage (Figure 3i).…”
Section: Resultsmentioning
confidence: 99%